Plasmid carriage in Vibrio vulnificus and other lactose-fermenting marine vibrios. - Davidson, L S (1986)
A total of 42 clinical and environmental isolates of Vibrio vulnificus were examined for plasmid carriage. Of these, only five (12%) harbored plasmids, which were of various molecular weights. In contrast, 20 of 32 (62.5%) unidentified lactose-fermenting Vibrio spp. were found to possess plasmids with masses of 2.1 to 150 megadaltons. In these isolates, multiple plasmids were common, with an average of 2.25 plasmids per plasmid-containing strain. Attempts to demonstrate a correlation with the plasmids identified in the various Vibrio spp. and a variety of phenotypic traits, production of several enzymes potentially involved in virulence, cytotoxicity for Chinese hamster ovary cells, and mouse lethality were unsuccessful. A correlation was observed, however, between the presence of a 6.5-megadalton plasmid and resistance to pteridine 0/129. It was concluded that V. vulnificus, unlike most other Vibrio spp., shows a general lack of these extrachromosomal elements.